2010
DOI: 10.1590/s1413-86702010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of leptospirosis: a retrospective study of 201 patients in a metropolitan city of Brazil

Abstract: INTRODUCTION: leptospirosis is a zoonosis of worldwide importance. The disease is endemic in Brazil. This study was conducted to describe the clinical and laboratory presentation of leptospirosis in a metropolitan city of Brazil. METHODS: this is a retrospective study including 201 consecutive patients with leptospirosis admitted to tertiary hospitals in Fortaleza, Brazil, between 1985 and 2006. All patients had clinical and epidemiological data suggestive of leptospirosis, and positive laboratorial test for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
25
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 36 publications
6
25
0
3
Order By: Relevance
“…The most frequent laboratory abnormalities in the patients with leptospirosis were thrombocytopenia, leukocytosis and transaminase elevation, as well as low hematocrit and hemoglobin levels (21). These abnormalities were also observed in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most frequent laboratory abnormalities in the patients with leptospirosis were thrombocytopenia, leukocytosis and transaminase elevation, as well as low hematocrit and hemoglobin levels (21). These abnormalities were also observed in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…These authors reported that patients with leptospirosis presented fever (96.5%), headache (74.6%), myalgia (92.5%), jaundice (94.5%), vomiting (71.6%), dehydration (63.5%) and chills (62.2%) (21). It is worth emphasizing that of the five patients who were positive for leptospirosis, three were hospitalized, where they probably developed some of the most severe forms of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by species of Leptospira, and transmitted to humans by direct contact with infected tissues or contaminated urine, or indirectly by contact with contaminated water or soil. Mammalian reservoirs are the main distributors, and although rodents are the most important reservoir, other animals, including livestock, wild and domestic animals may excrete leptospires in their urine and, therefore, be a potential source of infection [1][2][3] . Leptospirosis is associated with occupational and recreational exposure, usually occurring as endemic in rural areas with outbreaks associated with floods 1,3 .…”
mentioning
confidence: 99%
“…Este estudio incluyó 119 pacientes hospitalizados con diagnóstico de leptospirosis, en quienes se encontró una mayor frecuencia de complicaciones, especialmente falla hepática y síndrome de Weil, y una mortalidad general similar a la reportada en Colombia, pero inferior a la informada en algunas series de casos en otros países (22)(23)(24)(25)(26)(27)(28)(29). Se encontró, además, que cerca del 10 % de los pacientes no recibió tratamiento antibiótico a pesar de encontrarse hospitalizado.…”
Section: Discussionunclassified
“…Aunque la frecuencia de complicaciones fue superior a la descrita en la mayoría de las series, la mortalidad no excedió la informada en otros estudios colombianos y en el Sistema Nacional de Vigilancia en Salud Pública (1,5 a 5 %) (6,15,18,22,24,31), y fue inferior a la reportada en las series de casos en otros países (7 a 22 %) (23)(24)(25)(26)(27)(28)(29)32,33). Esta disociación entre una mayor frecuencia de complicaciones y una menor mortalidad es difícil de explicar, especialmente si se tiene en cuenta el gran número de pacientes que presentó síndrome de Weil, complicación asociada con una mayor mortalidad (32)(33)(34).…”
Section: Discussionunclassified